(untitled) (Journal of Scientific Research, 2023)
In the present paper, we considered Bianchi type-II space-time in the presence of a macroscopic body in the self-creation theory formulated by Barber. The relation between metric coefficient and state equation has helped present the exact cosmological model in theory. The features, stability, and some physical & kinematical properties of the obtained model are also discussed.